Pengembangan Media Pembelajaran Kamus Digital Bahasa Arab terhadap Motivasi Belajar Bahasa Arab Siswa MTs Kelas VIII - Rochim, Amelia Nur; Mubasyiroh, Nabilatun; Annisa, Annisa; Hasby, Muh. Subky (DIMAR: Jurnal Pendidikan Islam, 2025)
Currently, the world of education has various problems, one of which is the learning process, especially the monotonous Arabic language subject. This makes students less interested in the learning process. So that in the learning process requires new innovations such as the use of learning media that attract students' attention and also make it easier for students to learn Arabic. One suitable learning media is a digital dictionary that contains vocabulary in Arabic language textbooks. Therefore, this study aims to develop learning media in the form of a digital dictionary "hubbabah" to facilitate Arabic language learning. In the research process, researchers used the development method (R&D) with the 4-D model (definition, design, develop, disseminate). This digital dictionary is expected to be interesting and useful for students, and can be accessed at any time. Based on expert validation, this media is declared very valid with minor revisions. The results of the study showed an increase in student learning motivation, with an average questionnaire reaching 81% while the average student pretest score of 27% increased to 86.29% in the post-test. The level of student satisfaction with this digital dictionary reached 82%. Thus, the digital dictionary “Hubbabah” has proven to be effective in improving students’ motivation and learning outcomes in Arabic.